The South Seaman: An Incident in the Sea Story of Australia : 1901 - Becke, Louis, 1855-1913 (Salt Lake City, UT : Project Gutenberg, 2008)
"The South Seaman: An Incident in the Sea Story of Australia" by Louis Becke is a thrilling maritime tale likely written in the early 20th century. This novella recounts a gripping account of mutiny and survival aboard a ship sailing from South America to Australia. The story delves into the dangers faced by sailors in the Pacific during a time when navigation was perilous and the waters were often inhabited by unscrupulous characters. The narrative follows the brig "Indefatigable", once known as the "Calder", as it embarks on a dangerous journey after a mutiny orchestrated by a group of treacherous Chilean sailors. The protagonist, the first mate Loftgreen, finds himself battling both the chaos onboard and the survival instinct within himself as he faces assassination attempts from the mutineers. Meanwhile, the second mate, Todd, along with some crew members, manages to escape in a lifeboat, leading to their own perilous journey through the Pacific Islands. Ultimately, the story highlights themes of bravery, betrayal, and the harsh realities of life at sea, culminating in a dramatic resolution as the mutineers are apprehended and justice is served. (This is an automatically generated summary.)
Release date is 2008-04-19
Produced by David Widger
Keywords: Essays; Mutiny